Phase-pure M1 MoVNbTeOx/TiO2 nanocomposite catalysts: high catalytic performance for oxidative dehydrogenation of ethane. Issue 4 (17th January 2022) - Dang, Dan; Chen, Yuxin; Chen, Xin; Feng, Kai; Yan, Binhang; Cheng, Yi
Abstract : The introduction of TiO2 can improve the catalytic performance of phase-pure M1 MoVNbTeO x in the ODHE process, in which the STY enhancement of M1/40TiO2 at 400 °C and W / F = 7.55 gcat h molC2 H6 −1 reached ∼76%. Abstract : The catalytic performance of the phase-pure M1 MoVNbTeO x catalyst is enhanced by introducing TiO2 in oxidative dehydrogenation of ethane (ODHE). The space–time yield (STY) of the M1/TiO2 composite catalyst increases significantly with increasing TiO2 content (normalized to M1), in which the catalyst containing 40 wt% TiO2 presents the best ethylene productivity with an enhancement of 76.3% compared to phase-pure M1 at 400 °C in the ODHE process. Meanwhile, the stability of the M1/TiO2 catalysts is also demonstrated by the stable crystal structure and surface morphology of the used catalysts. The results of pulse reaction experiments further reveal that the introduction of TiO2 enhances the reduction/re-oxidation rate of lattice oxygen species in the catalysts thus improving catalytic performance.